Find the inverse function of g(x)=-2/(x+1)

### 1 Answer | Add Yours

We'll determine the inverse of g(x) in this way.

Let g(x) = y

y = -2/(x+1)

Now, we'll find x with respect to y. F

y(x+1) = -2

We'll remove the brackets and we'll get:

yx + y = -2

We'll isolate x to the left side and we'll get:

yx = -2 - y

We'll divide by y:

x = -(2+y)/y

Therefore, the inverse function is: f^-1(x) = -(2+x)/x

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes